Nanofibers obtained by electrospinning of BaTiO3 particles dispersed in polyvinyl alcohol and ethylcellulose - Ávila,Humar A. (2013)
Barium titanate particles (100-300 nm) synthesized by hydrothermal method were dispersed in both polyvinyl alcohol (PVA) and ethylcellulose (EC) solutions. These suspensions were processed by electrospinning. When no particles were added, homogeneous polymeric nanofibers were obtained. Under certain conditions, polymeric suspensions of barium titanate particles were electrospun generating polymeric fibers with BT particles. The effect of a surfactant was also assessed over the formation of nanofibers. The BaTiO3 particles synthesized by hydrothermal method were characterized by X-Ray diffraction (XRD), field emission-scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM) and Raman spectroscopy. Fibers were characterized by scanning electron microscopy (SEM).